2007
DOI: 10.1177/1461445607075347
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting the form and use of reformulation markers

Abstract: This paper deals with the form and use of reformulation markers in research papers written in English, Spanish and Catalan. Considering the form and frequency of the markers, English papers tends to prefer simple fixed markers and includes less reformulators than Spanish and Catalan. On the contrary, formal Catalan and Spanish papers include more markers, some of which are complex and allow for some structural variability. As for use, reformulation markers establish dynamic relationships between portions of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 21 publications
(26 reference statements)
0
9
0
5
Order By: Relevance
“…As we can see from the following examples, the proposed typology of functions applies to both languages, since RMs operate cross-linguistically (Cuenca 2003, Cuenca & Bach 2007, Garcés Gómez 2009, Murillo 2007): I. Functions related to the interpretation of explicit content:…”
Section: Functions Of Rms In the Three Subcorporamentioning
confidence: 97%
See 2 more Smart Citations
“…As we can see from the following examples, the proposed typology of functions applies to both languages, since RMs operate cross-linguistically (Cuenca 2003, Cuenca & Bach 2007, Garcés Gómez 2009, Murillo 2007): I. Functions related to the interpretation of explicit content:…”
Section: Functions Of Rms In the Three Subcorporamentioning
confidence: 97%
“…She found, however, a higher overall frequency than in the study performed by Murillo (2007) and that attested in the present study, especially in the Spanish subcorpus: Cuenca found 47 RMs in her English subcorpus, which would amount to approximately 11.75 per 10,000 words, and 95 cases in her Spanish one (23.75 per 10,000 words). 7 As explained in a follow-up article (Cuenca & Bach 2007), it is important to take into account that the papers in this corpus are written versions of oral presentations in conferences, which could encourage the frequency of use of RMs and influence the types of RMs used.…”
Section: General Frequency Of Rms In the Three Subcorporamentioning
confidence: 99%
See 1 more Smart Citation
“…No obstante, tan solo ofrecen un recuento de conectores sin aportar si en sus respectivos corpus se hallan distintos valores de un determinado conector o simplemente uno de ellos. Sin embargo, si no los incorporamos a nuestros análisis, estos quedarán cojos, como muestran las escasas investigaciones que se han llevado a cabo cuando estos se han incorporado (Flores Acuña, 2003;Cuenca y Bach, 2007;Lira Dias, 2010;Simma, 2013; entre otros). Desgraciadamente, aunque estos estudios incorporan incluyen los distintos valores de determinados conectores que hallan en sus respectivos corpus, desconocemos con qué frecuencia encontramos cada uno de estos valores por lo que ignoramos si un determinado valor es uno de los principales o tan solo marginal.…”
Section: Justificaciónunclassified
“…O texto passa a ter um caráter autoexplicativo a partir do emprego de recursos de reescritura dos artigos científicos em notícias de PC (HYLAND, 2007 Neste artigo, focamos o processo de reformulação por meio do emprego de aposto e glosa. A literatura publicada sobre o tema (CIAPUSCIO, 2003;HYLAND, 2005HYLAND, , 2007HYLAND, , 2009LEIBRUDER, 2000;VANDE KOPPLE, 1985, CUENCA;BACH, 2007), bem como as análises prévias já realizadas (PRATES; SCHERER; MOTTA-ROTH; NASCIMENTO, 2008;MOTTA-ROTH;LOVATO, 2008;MOTTA-ROTH;LOVATO, 2009;, MOTTA-ROTH, 2009) corroboram a existência e a importância desses recursos, pois produzir um texto de popularização da ciência significa basicamente recontextualizar e reformular uma fonte de modo que a mesma seja compreensível e relevante para uma outra audiência, em um contexto discursivo que, apesar de previsível, difere daquele da fonte original (CIAPUSCIO, 2003, p. 210).…”
Section: Introductionunclassified